Factors involved in university student dropouts - Chui B., Heber (2025)
The study aimed to identify the factors that influence university dropout among students of the professional career of Veterinary Medicine and Animal Husbandry at Universidad Nacional del Altiplano de Puno, Peru. The research had a descriptive, explanatory and cross-sectional approach, carried out with 365 undergraduate students, 53.97% of whom were male (n = 197), with an average age of 21.3 ± 3.4 years. Alcohol consumption was assessed using the CAGE scale (α = 0.8), and the presence of depressive symptoms was determined by applying the CES-D scale (α = 0.93). The University Student Dropout Scale - EDEU (α = 0.96) was used to determine factors of university student dropout, and the Rosenberg test was applied to assess self-esteem (α = 0.95). The multiple logistic regression model showed that students with low self-esteem had a 4.114-fold increased risk (95% CI [2.144–9.631]; p<0.001) of dropping out of college compared to students with good self-esteem. Socioeconomic status, poor academic performance, and alcohol consumption were associated with a lower risk of dropping out of college.